Man-O-Pause Unraveling the truth behind andropause and its on the family and society in Tacloban City. - Gabriola, Meikko A., et al; Villaflor Dyezebel Rose V. (Meikko Gabriola, 2011)
This study sought to determine the existence of andropause in men as well as in broadening the knowledge of individuals about this matter, providing knowledge of local men's views and experiences of their symptoms, their experiences of how it affects their relationship with their family, their careers and the workplace. An interpretive social science approach that relies on a subjective relationship between the research participants and the researchers was employed. Three focus groups of respondents with age range of 40-50, 51-60, and 61-70 years old were the samples of this study. Five men were selected from each age range making a total of 15 participants. Results showed a decline to physical strength and power that in one way or another affected their quality of life enabling them to do less than they were used to. Their feelings of anxiety and increase in stress led to changes in sleeping patterns. A decline in power, may it be physical, psychological, and sexual, was seen as the most prominent one which emerged in the analysis of the data gathered. It came as no surprise when the participants believed that it was set off by a decline in physical power, cascading into waning psychological--emotional power, sexual power, relationship power, and work power. In conclusion, middle-aged men experience diverse changes in their bodies, particularly on the physical, psychological and sexual aspects. These symptoms occur gradually. A lot of men struggle on finding out what might have caused the changes they experience as they age. Of course, some would say that it's just part of a natural process caused by aging. But apart from this, a phenomenon known as andropause had emerged. This is an interplay of not just biological transformations but also the psychological features as well.